A first-principles study on Al-doped ZnO growth polarity on sapphire (0001) surface. (26th July 2016) - Yang, Ping; Gao, Qian; Hu, Zhen-Peng; Zhang, Li-Xin
Abstract: Based on the first-principles method, the polarity inversion mechanism of Al-doped ZnO grown on sapphire (0001) substrate was investigated. This study revealed that the Al dopant tends to float on the surface of the buffer layer and leads to form ZnO nucleation islands of Zn-polarity without changing in-plane orientation. Finally, these islands evolve to wall-like nanostructure with Zn-termination. The results can explain the reason of the polarity inversion phenomenon in the experiment and supply more information for controlling the ZnO growth polarity.